Exchange rate forecasting and the performance of currency portfolios - Jesus Crespo Cuaresma; Ines Fortin; Jaroslava Hlouskova (Institute for Advanced Studies (IHS), 2017)
We examine the potential gains of using exchange rate forecast models and forecast com- bination methods in the management of currency portfolios for three exchange rates, the euro (EUR) versus the US dollar (USD), the British pound (GBP) and the Japanese yen (JPY). We use a battery of econometric specifications to evaluate whether optimal currency portfolios implied by trading strategies based on exchange rate forecasts out- perform single-currency and the equally weighted portfolio. We assess the differences in profitability of optimal currency portfolios for different types of investor preferences, different trading strategies, different composite forecasts and different forecast horizons. Our results indicate that the benefits of integrating exchange rate forecasts from state-of-the-art econometric models in currency portfolios are sensitive to the trading strategy under consideration and vary strongly across prediction horizons.
Keywords: G02; G11; E20; 330; currency portfolios; exchange rate forecasting; trading strategies; profitability